Global Statement on Air Pollution and Health: Opportunities for Africa - Caradee Y. Wright; Angela Mathee; Stuart Piketh; Kristy Langerman; Tafadzwa Makonese; Siyavuya Bulani; Himla Soodyall (Ubiquity Press, 2019)
The editorial speaks to the Global Statement on Air Pollution and Health and How it may assist African countries to eliminate air pollution-related health impacts.